The Structure of Intertemporal Preferences under Uncertainty and Time Consistent Plans - Johnsen, Thore H.; Donaldson, John B. (Econometrica, 1985)
Analyse de la structure des preferences intertemporelles, necessaire pour obtenir une planification consistante